"States" of informality in post-socialist Europe (and beyond). (1st September 2016) - Polese, Abel; Morris, Jeremy; Kovács, Borbala
Abstract: This article explores the main debates and works that underpin the theoretical conceptualization of this special issue and documents the exponential growth of literature on informality both globally and, especially, in post-socialist spaces. In spite of this growth, informality is still relatively understudied considering how widespread and significant a phenomenon it has become. In particular, if we go beyond a merely economistic view of the phenomenon, one could argue that an understanding of informality explains a variety of social responses and the number of cases where we have been able to apply an informality framework is perhaps very telling. Debates remain too bounded by one of two paradigms: either recourse to geographic particularism or exceptionalism or ongoing debates on transition or transformation (the appropriateness of 'posting' socialism). To break with this attitude, we suggest with this special issue that study of informality needs to build into itself a middle-field theory explaining its endurance which acknowledges both specificities of social action arising from common(ish) pasts and experience of change after 1989/91 leading to translatable presents, as well as these societies' positioning as mediating sites of neocapitalism between the Global North and South, with such a theory being a key articulation of the multiple modernities thesis.